2012
DOI: 10.2147/ijn.s25761
|View full text |Cite
|
Sign up to set email alerts
|

How can micelle systems be rebuilt by a heating process?

Abstract: The aim of this work was to evaluate how an aqueous micellar system containing Amphotericin B (AmB) and sodium deoxycholate (DOC) can be rebuilt after heating treatment. Also, a review of the literature on the physicochemical and biological properties of this new system was conducted. Heated (AmB-DOC-H) and unheated (AmB-DOC) micelles were then diluted at four different concentrations (50 mg · L −1 , 5 mg · L −1 , 0.5 mg · L −1 , and 0.05 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Mild heating of Fungizone ® (20 min at 70 • C) was found to increase the thermodynamic stability of the formulation and to improve its therapeutic index by producing a super aggregated and less toxic form of AmB while retaining antifungal efficacy [57,[84][85][86][87][88][89][90]. Heat-induced superaggregation of AmB was shown to modify its distribution among the serum lipoproteins and to attenuate AmB-stimulated production of TNF-α and other pro-inflammatory mediators in human THP-1 monocytes in vitro [86,91], which may contribute to its reduced cytotoxicity against host cells in vivo in experimental animal mycoses [86,87,89,92].…”
Section: Commercial Amphotericin B Lipid Formulationsmentioning
confidence: 99%
“…Mild heating of Fungizone ® (20 min at 70 • C) was found to increase the thermodynamic stability of the formulation and to improve its therapeutic index by producing a super aggregated and less toxic form of AmB while retaining antifungal efficacy [57,[84][85][86][87][88][89][90]. Heat-induced superaggregation of AmB was shown to modify its distribution among the serum lipoproteins and to attenuate AmB-stimulated production of TNF-α and other pro-inflammatory mediators in human THP-1 monocytes in vitro [86,91], which may contribute to its reduced cytotoxicity against host cells in vivo in experimental animal mycoses [86,87,89,92].…”
Section: Commercial Amphotericin B Lipid Formulationsmentioning
confidence: 99%
“…These results indicate that the AmB entrapped inside of the hydrogel structure keeps its antifungal activity, just as free AmB, while the PVA–H did not show any antifungal activity, corroborating with the idea that AmB stands with its pharmacological activity unaltered and the residual cross-linking quantities were negligible to show antifungal activity or severe cytotoxicity. It has been reported that the affinity of AmB to the ergosterol on fungi membranes is strongly dependent on its aggregation state [80,81]. This phenomenon could be the main reason behind the enhanced antifungal activity of PVA–AmB compared to the free form of the drug.…”
Section: Resultsmentioning
confidence: 99%
“…Hemolytic activity was performed according to Silva-Filho et al [ 64 ] with some modifications. A healthy adult donor provided blood for the in vitro experiments.…”
Section: Methodsmentioning
confidence: 99%